Study Participation of Dairy Cattle Famers in Pollution Control Management to the Product of Milk - Hendarto, Eko; Mastuti, Sri (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 1999)
Based on activity, the population on dairy cattle, can be divided into two kinds i.e. pollution around the farm and pollution on the product ofÂ milk. In order to eliminate the potency of the pollution, then, the manages to control it is urgently needed. The research was conducted by the farmers in banyumas Regency, Central Java Province, the has aids dairy cattle from government. The aim of the research was to know of participation to pollution control management on the product of milk. Survey method and descriptive analysis were used in this research. The technique of sampling used to collected data by Multy Stage Purposive Random Sampling from Sutrisno (1981). The independent variable of this research was social characteristic of the farmers i.e. mean of livelihood, income of cattlemen, participation of cattlemen on social institution and type of animal production, meanwhite, the dependent variable was the manages of pollution control the product of milk. To know the level ofÂ participation control of pollution the milk product by crossing of the between variable table. Based on the analyses, it was found that the participation farmers to the manages to pollution control on the product of milk was in the level ofÂ âgoodâ. (Animal Production 1(2): 63-74 (1999)Â Key Words: Participation levels, pollution, milk.